Kepemimpinan, Beban Kerja dan Burnout terhadap Kinerja Karyawan Perusahaan Garment di Kabupaten Tangerang - Erna Lika Kabdiyono; Didin Hikmah Perkasa; Muhamad Ekhsan; Muhammad Al Faruq Abdullah; Wenny Desty Febrian (Journal of Management and Bussines (JOMB), 2024)
This research aims to explore the influence of leadership, workload and burnout on employee performance in garment companies in Tangerang Regency. The research design used is a causal relationship with a quantitative approach, which aims to find cause-and-effect relationships between the variables studied. Data collection was carried out by distributing questionnaires to garment company employees using a Likert scale as a measuring tool. The population of this research was 74 employees of garment companies in Tangerang Regency, who were also used as research samples using saturated sampling techniques. The data analysis method used is Structural Equation Modeling (SEM) with Partial Least Squares (PLS). Data processing involves measurement tests, structural tests, and hypothesis tests. The research results show that leadership has a positive and significant influence on employee performance. However, workload and burnout do not have a significant influence on employee performance. Thus, these findings highlight the importance of the role of leadership in improving employee performance in garment companies. Although workload and burnout do not significantly influence employee performance in the context of this research, this does not reduce the need to pay attention to and manage these factors in the context of human resource management. Keywords: Workload, Burnout, Employee Performance, Leadership